DARI PACHT PASAR KE PASARFONDS: PASAR PONTIANAK DALAM KEBIJAKAN EKONOMI KOLONIAL BARU PADA AWAL ABAD XX - Dana Listiana (Pusbindiklat - LIPI, 2014)
This research discusses about Pasar Pontianak in the changing of management system during colonial time. The purpose of this research is to analyze the background for deleting pacht pasar in 1919 and the effect after being directly handled by the local government through pasarfonds. To do the research, historical research method was used. The result of this research shows that the changing in the system was caused by the increasing number of workers and colonial government’s worries of the new political power based upon the economic strength of Tionghoa society as a main drive to trading in market. Meanwhile, the new colonial economic policy had triggered the growth in the market-forming elements, which were; the management system, places, trading subjects, com- modities, and trading activities.